2021
DOI: 10.1177/1357633x211058330
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of telehealth curriculum: National survey of clinical education leaders

Abstract: Introduction In response to the COVID pandemic and the rapid changes in delivery of and education on telehealth services, the Research Committee of the Alliance of Clinical Education (ACE) surveyed its multidisciplinary group of medical educators to determine how telehealth was being taught pre-COVID versus during-COVID. Methods An online survey was developed by the ACE Research Committee and sent via email to the ACE delegation. The objective of the survey was to determine changes in telehealth curriculum for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…7 In 2018, 76% of US hospital systems implemented some form of telehealth 7 to address existing deficiencies related to healthcare provider shortages and remote geographical locations and increase equitable access to care among diverse populations. [8][9][10] Telehealth services are viable options within healthcare and have increased accessibility, reduced service barriers, and supported emergency response events. 11,12 The inception of teledentistry has emerged as a subspeciality of the telemedicine domain 13,14 following the rapid progression of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In 2018, 76% of US hospital systems implemented some form of telehealth 7 to address existing deficiencies related to healthcare provider shortages and remote geographical locations and increase equitable access to care among diverse populations. [8][9][10] Telehealth services are viable options within healthcare and have increased accessibility, reduced service barriers, and supported emergency response events. 11,12 The inception of teledentistry has emerged as a subspeciality of the telemedicine domain 13,14 following the rapid progression of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth options have been implemented in other healthcare fields to increase patient access to care for acute and chronic disease management 7 . In 2018, 76% of US hospital systems implemented some form of telehealth 7 to address existing deficiencies related to healthcare provider shortages and remote geographical locations and increase equitable access to care among diverse populations 8–10 . Telehealth services are viable options within healthcare and have increased accessibility, reduced service barriers, and supported emergency response events 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Despite pharmacists’ positive patient contributions on the telehealth care team [ 4 , 5 ], there remains a deficit in telehealth integration into didactic education within pharmacy curricula [ 6 ]. Compared to professional pharmacy programs, there was also a dearth in medical school curricula of the incorporation of telehealth instruction into didactic education prior to the pandemic [ 7 ]. Chike-Harris et al compared different healthcare training programs and found significant discrepancies in the consistency and depth of telehealth content between curricula [ 6 ].…”
Section: Introductionmentioning
confidence: 99%